A new formulation for transient response optimization of structures based on constraint aggregation functions. Issue 9 (2nd September 2022) - Couceiro, I.; París, J.; Ramírez, L.; Navarrina, F.
Abstract : This article proposes a new formulation for the treatment of time-dependent constraints in the transient response optimization of structures. The novel method is based on constraint aggregation functions. However, instead of lumping the constraints in the physical domain, the method condenses the information of the time-dependent constraints into one equivalent function while retaining information about the point-wise constraints. The formulation is gradient compatible and allows a considerable reduction of the optimization problem. Two versions of the Kreisselmeier–Steinhauser function are studied. The formulation is tested on the size optimization of truss and framed three-dimensional structures subjected to dynamic loads. The methodology is tested in very-large transient response optimization problems in order to check its efficiency. Results show that the formulation is able guarantee the fulfilment of the constraints in the whole time interval studied. The size of the transient response optimization problem is highly reduced, allowing a reduction of the computational resources needed.